Effects of the physical form of starter feed on the intake, performance, and health of female Holstein calves - Í.R.R. Castro; G.B.C. Leite; I.F. Carrari; L.N.C. Silva; J.C.C. Chagas; D.D. More; M.I. Marcondes (Animal)
Available literature on the effect of various physical forms of starter feed (PFSF) on calf performance is conflicting. Thus, this study aimed to investigate the effect of the PFSF on feed intake, growth performance, blood metabolites, and the health of dairy calves. Twenty-four female Holstein calves (5-d-old; 40.4 ± 3.86 kg BW; mean ± SD) were used in a completely randomized block design. Calves were individually housed and randomly assigned to the treatments (n = 12 calves/treatment): (1) textured starter feed (TSF, a mix of pelleted ingredients and whole-kernel corn) and (2) pelleted starter feed (PSF). Both starter feeds had the same ingredients, nutrient compositions and pellet die size. Calves were fed the same milk replacer and weaned in a step-down scheme at 67 d. Health was evaluated daily until weaning. Treatments did not affect starter feed intake, water intake, BW, ADG, withers height, or clinical signs of disease (loss of appetite, ear position, and cough incidence). Nonetheless, scores for abnormal attitude (P = 0.01), ocular discharge (P < 0.01), total respiratory disease (P = 0.02), and fecal consistency (P = 0.04) of PSF-fed calves were higher than those TSF-fed. Based on that, TSF-fed calves exhibited a higher non-disease probability compared to PSF over time. Calves TSF-fed sorted against small particles (0.425-mm sieve; P = 0.01). Coincidently, PSF-fed animals sorted for small particles in the same sieve sizes. No major changes in blood profile were found (P > 0.05). In conclusion, starter feeds containing whole-kernel corn as a texturizer did not improve the intake and performance of dairy calves compared with pelleted starter feed; however, improvements were observed in health scores and non-disease probability of calves fed textured starter feed.